Natural Alternatives in the Treatment of Colorectal Cancer: A Mechanisms Perspective - Karen Vanessa Fernandez-Muñoz; Cuauhtémoc Ángel Sánchez-Barrera; Marco Meraz-Ríos; Jose Luis Reyes; Eloy Andrés Pérez-Yépez; Maria Teresa Ortiz-Melo; Luis I. Terrazas; Monica Graciela Mendoza-Rodriguez (Biomolecules)
Colorectal cancer (CRC) is one of the deadliest neoplasia. Intrinsic or acquired resistance is the main cause of failure of therapy regimens that leads to relapse and death in CRC patients. The widely used chemotherapeutic agent 5-fluorouracil (5-FU) remains the mainstay for therapeutic combinations. Unfortunately, chemotherapeutic resistance and side effects are frequent events that compromise the success of these therapies; the dysregulation of enzymes that regulate 5-FU metabolism increases the expression and activity of efflux pumps. Additional tumor cell adaptations such as epithelial–mesenchymal transition (EMT), autophagy shaping of the tumor microenvironment, and inflammation contribute to chemoresistance. Finding new strategies and alternatives to enhance conventional chemotherapies has become necessary. Recently, the study of natural compounds has been gaining strength as an alternative to chemotherapeutics in different cancers. Curcumin, trimethylglycine, resveratrol, artemisinin, and some helminth-derived molecules, among others, are some natural compounds studied in the context of CRC. This review discusses the main benefits, mechanisms, advances, and dark side of conventional chemotherapeutics currently evaluated in CRC treatment. We also analyzed the landscape of alternative non-conventional compounds and their underlying mechanisms of action, which could, in the short term, provide fundamental knowledge to harness their anti-tumor effects and allow them to be used as alternative adjuvant therapies.